Phorbol esters enhance the cyclic GMP response of T84 cells to the heat-stable enterotoxin of Escherichia coli (STa). - Weikel, C S (1990)
We examined the effect of protein kinase C (PKC) activation on the cyclic GMP response to heat-stable enterotoxin (STa) in a colonic carcinoma intestinal epithelial cell line, T84 cells. Our results demonstrate that the active phorbol ester analog, phorbol dibutyrate, but not the inactive alpha-phorbol dibutyrate, acts synergistically with STa to elevate cyclic GMP in intact T84 cells. The effect is observed in the absence or presence of the phosphodiesterase inhibitor, isobutylmethylxanthine, which suggests that phorbol dibutyrate modifies cyclic GMP synthesis rather than cyclic GMP degradation. In contrast to several systems in which prolonged treatment with phorbol ester desensitizes PKC-mediated responses, the cyclic GMP response in T84 cells is not diminished by prolonged treatment of T84 cells with phorbol dibutyrate. Also, transient treatment of T84 cells with phorbol dibutyrate enhances subsequent STa-stimulated cyclic GMP accumulation. These observations suggest that PKC activation produces a long-lived signal in T84 cells which enhances cyclic GMP accumulation in response to STa. Second messenger "cross talk" [T. Yoshimasa, D. R. Sibley, M. Bouvier, R. J. Lefkowitz, and M. G. Caron, Nature (London) 327:67-70, 1987] may be important in the pathogenesis of diarrheal disease.